Penerokaan Konsep Al-tawriq Dalam Pencairan Aset Wakaf - Fuadah Johari; Wan Abdul Fattah Wan Ismail; Muhammad Aunurrochim Mas'ad Saleh; Hanim Hj Misbah; Ahmad Syukran Baharuddin; Nurul Asikin Abdul Razak (Usim Press, 2024)
Al-Tawriq, which liquidity and sells waqf assets, is mooted by Mohd Daud Bakar (Global Syariah Figure) to address unproductive, idle, no commercial value and lack of funds for waqf assets, aimed at financing maintenance or development costs. Despite waqf assets need to be maintained as a fundamental principle of waqf, based on the hadith of the Prophet Muhammad, al-Tawriq is permissible according to ijtihad by Qadi's or syariah advisory panel. Therefore, the main purpose of this study is to explore to what extent, Islamic law allows the waqf assets to be liquidated by selling those properties. Using the qualitative method based on the analysis of the textual content of the classic Fiqh reference books, this study will explore the fundamental principles that allow this al-Tawriq method to be implemented. The study found that there are some basic principles that support al-Tawriq to be applied. The study proposes al-Tawriq to be used as one of the solutions to the development of waqf assets in Malaysia, aimed at enhancing the quality of waqf assets by establishing cash liquidity as a new source of funding for maintenance or development expenditure. It is important to ensure that waqf assets become more productive, beneficial for beneficiaries in their hereafter and have a positive impact on the development and economy of Muslims and humanity.